Confirmatory factorial analysis of Steinberg's Parenting Style Scale: Preliminary construct validity - Merino Soto, César (2004)
The present study tried to find evidences of construct validity and interna! reliability for the Parenting Styles Scale of L. Steinberg. The instrument was applied in a sample of 224 adolescents from 11 to 19 years old from a public school of Lima. With a strategy of multiple group confirmatory factor analysis, the three-subscale structure (Commitment, Psychological Autonomy and Behavior Control/Supervision) was in general stable, although the theoretical grouping of the items was influenced by the distribution of the item. The alpha reliability reached marginal levels and the probable impact of the random error was recognized. Results show that this instrument is a potential too! for research, but these findings are preliminary and additional studies are required to evaluate the generalization of the analysis.